ANALISIS KOMPARATIF PEMAKAIAN TWO-WAY SLAB DAN FLAT SLAB TERHADAP KINERJA SEISMIK GEDUNG “LP” - Gusanto, Steven; Sandjaya, Arif (JMTS: Jurnal Mitra Teknik Sipil, 2025)
Indonesia is located in a seismically active region due to the presence of the Eurasian Plate and the Indo-Australian Plate. This means that buildings and non-building structures must be designed to withstand seismic forces. One of the critical elements in resisting earthquakes in a building is the floor slab. In addition to resisting seismic forces, the floor slab also serves as a walking and activity area for people. There are several types of floor slab construction, for example flat slab and two-way slab. When considering which type of floor slab construction to use in a building, a seismic performance analysis of the slabs is necessary to evaluate their effectiveness under gravitational loads and lateral forces. This study examines seismic performance indicators such as base shear, story shear, story displacement, and story drift that occur in each type of floor slab. The dimensions and specifications of the slabs used will be adjusted according to minimal requirements. The seismic analysis is conducted in three dimensions using response spectrum analysis. Based on the analysis results, it can be concluded that two-way slabs exhibit higher seismic resistance compared to flat slabs, as they result in greater base shear, story shear, story displacement, and story drift. Consequently, the design of buildings with two-way slabs will be safer against larger seismic loads than those with flat slabs. Abstrak Indonesia berada pada daerah rawan bencana gempa karena dilewati oleh lempeng Eurasia dan lempeng Indo-Australia. Hal ini berarti bangunan gedung maupun non gedung hraus dirancang menahan gaya gempa. Salah satu elemen yang membantu menyalurkan beban lateral gempa adalah pelat lantai. Selain itu, pelat lantai juga berfungsi sebagai tempat berpijak dan beraktivitas bagi manusia. Terdapat beberapa jenis konstruksi pelat lantai, contohnya adalah flat slab dan two-way slab. Dalam mempertimbangkan jenis konstruksi pelat lantai yang akan digunakan pada bangunan, dibutuhkan analisis kinerja seismik dari pelat yang dapat bekerja dan seberapa optimal mereka saat dibebani gravitasi dan gaya lateral. Penelitian ini mengkaji kinerja seismik seperti base shear, story shear, story displacement, dan story drift yang terjadi pada masing-masing jenis pelat lantai. Dimensi dan spesifikasi pelat yang digunakan akan disesuaikan dengan kebutuhan minimal. Analisis gempa dilakukan secara tiga dimensi menggunakan analisis respons spektrum. Berdasarkan hasil analisis dapat disimpulkan bahwa two-way slab memiliki ketahanan seismik yang lebih tinggi dibandingkan dengan flat slab karena menghasilkan base shear, story shear, story displacement, dan story drift yang lebih besar. Hal ini mengakibatkan desain dari bangunan konstruksi two-way slab akan lebih aman terhadap beban gempa yang lebih besar dibandingkan dengan flat slab.